Development of artemisinin resistance in malaria therapy. (August 2019) - Naß, Janine; Efferth, Thomas
Graphical abstract: Abstract: Malaria affects 200 million people worldwide. Today, the most successful treatments are artemisinin-based combination therapies (ACT). Resistance has already been described for the elder anti-malarials chloroquine, sulfadoxine–pyrimethamine and mefloquine. Unfortunately, over the last few years there has also been an emerging resistance to the successfully used drug artemisinin, especially in African and Asian countries. A systematic PubMed literature research was conducted for studies published between January 2002 and December 2018. Despite ACTs continue to be first line treatment, the number of studies is rising reporting on artemisinin resistance mutations. Most publications reported on kelch13 mutations (45 studies), the second most frequent mutations were found in pfmdr1 (32 studies). PfATPase6 mutations have been mainly studied in Asian countries (4 of 6 studies). Bearing this in mind, there is a pressing need to further examine the role and spread of mutations conferring artemisinin resistance. A further decline of treatment efficacy could result in increased rates of malaria-related deaths.